Feasibility Analysis Of Philodendron Selloum Ratu Leaf Cut Business In Sumberjo Village, Sanankulon District, Blitar Regency - Prayudhi, Luhur Aditya; Zamrodah, Yuhainin (Agrikan Jurnal Agribisnis Perikanan, 2022)
Commodities of florikutura from potted ornamental plants, cut flower ornamental plants, leaf ornamental plants and garden plants. Especially for leaf ornamental plants, it consists of cut leaves and leaf ornamental plants in pots. Cut leaves are ornamental plants whose leaves are used to complement flower arrangements or fillers. The sales volume of cut leaves in Indonesia has increased. The types of cut leaves to complement the series in recent years have experienced a lot of increase in price, volume and types of leaves. The Onchi Orchid's Farmer Group, Sumberjo Village, Sanankulon District, Blitar Regency is one of the producers of Philodendron selloum Ratu cut leaves. It is expected that Philodendron selloum Ratu cut leaf farming can be developed further. For the analysis results of Philodendron Selloum Ratu cut leaf farming, the net profit obtained is Rp 7.790.000. The results of the financial analysis using the RC ratio obtained 1.16 R/C > 1 means this farming is efficient to implement.